Exclusive Breastfeeding to Infant Nutritional Status - Mareza Yolanda Umar; Linda Puspita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Infancy starts from 0-12 months and is characterized by rapid growth and physical changes as well as changes in nutritional requirements. There is still a lack of breast milk as the baby's first meal. In fact, the reduction of child nutrition can lead to child malnutrition and underdevelopment (stunted growth). The purpose of this study is to determine the relationship between exclusive breastfeeding and infant nutritional status. The study used a cross-sectional design analysis and investigation method to study the success of breastfeeding on nutritional status. The object of the study is 7-12 months old babies, a total of 113 people. There is an association between exclusive breastfeeding and nutritional status, with a P value of 0.000 and an OR value of 5.938, which means that infants who are not exclusively breastfed have a 5938 times higher risk of being in a low nutritional status. Puskesmas should play an important role in supporting exclusive breastfeeding by actively providing counseling involving pregnant women, breastfeeding mothers, husbands and families about the importance of exclusive breastfeeding so that breastfeeding mothers can give exclusive breastfeeding to their children. The midwives are expected to play an active role in acting as breast milk counselors so that exclusive breast milk can be carried out.Masa bayi dimulai sejak umur 0-12 bulan yang ditandai dengan perkembangan dan perubahan jasmani yang cepat disertai dengan evolusi dalam keperluan zat gizi. pemberian ASI sebagai makanan kesatu bayi masih kurang. Padahal, penurunan gizi anak dapat mengakibatkan anak bergizi kurang sampai buruk dan tumbuh pendek (stunting). Tujuan riset ini ialah diketahuinya hubungan ASI khusus terhadap kedudukan gizi bayi. penelitian memakai metode Survey analitik memakai rancangan cross sectional, yang menganalisis keberhasilan ASI Eksklusif terhadap kedudukan gizi. Subjek riset ini ialah ibu yang mempunyai bayi umur 7–12 bulan dengan jumlah narasumber 113orang, Didapatkan hubungan antara ASI khusus dengan kedudukan gizi dengan P value 0.000 dan OR 5.938 yang berarti bayi yang tidak ASI Eksklusif berisiko 5,938 kali lebih banyak mengalami kedudukan gizi rendah. Hendaknya puskesmas berperan penting dalam menyokong pemberian ASI khusus dengan teknik berperan aktif menyerahkan penyuluhan yang melibatkan ibu hamil, ibu menyusui, suami dan keluarga mengenai pentingnya ASI eksklusif supaya ibu menyusui dapat menyerahkan ASI khusus kepada anaknya. Bidan desa diinginkan dapat berperan aktif dalam menjalani perannya sebagai konselor ASI supaya ASI khusus dapat terlaksana.